Transplante de células tronco mesenquimais melhora a função motora e modula marcadores de atrofia muscular em ratos diabéticos - Sabadine, Maria Augusta (Universidade Federal de São Carlos, 2017)
Hyperglycemia causes sensorimotor disorder and muscle atrophy for which there is no satisfactory therapy. Stem cell therapy is an attractive strategy for diabetic complications due to its capacity to differentiate into other cell types. This study aimed to evaluate the effects of mesenchymal stem cell (MSC) transplantation on neuromuscular function, skeletal muscle morphology and the expression of markers associated with muscle atrophy. Diabetes Mellitus (DM) was induced by Streptozotocin in Wistar rats. The diabetic animals received four i.p. injections (one injection per week) of bone marrow-derived MSC (BM-MSC) or vehicle (DM). Tibialis Anterior muscles were collected for morphological analysis and for the determination of mRNA (Atr-1, MuRF-1, Mst, MyoD, IGF-1, TWEAK, Fn-14, NFkB and p38 MAPK) and protein expression (Atr-1, MuRF-1). The Von Frey test and footprint analysis improved significantly in the BM-MSC group compared with the DM group. Muscle mass decreased in DM animals and did not change after transplantation. The number of central nuclei and connective tissue increased in the DM group (14,05% e 34,07%, respectively) and decreased in the BM-MSC group (7,53% e 18,23%, respectively). Muscle mRNA expression of Atr-1 and MuRF-1 were significantly higher in the DM group than the Control animals and decreased in BM-MSCs animals. The NF-κB and Fn-14 mRNA expression was significantly higher in the DM group than in the Control group. Fn-14 expression increased after transplantation. The MyoD mRNA expression decreased in both DM and BM-MSCs animals. The p38 MAPK mRNA expression was significantly higher in BM-MSCs than in the DM and Control animals. The Mst, IGF-1 and TWEAK mRNA expression did not differ among the groups. The Atr-1 and MuRF-1 protein expression increased in the DM group and the Atr-1 protein expression decreased in BM-MSCs animals. The results demonstrate the improvement of motor function and the modulation of Atr-1, MuRF-1, Fn-14 and p38 MAPK in skeletal muscle by BM-MSC transplantation in diabetic rats.
Mesenchymal stem cell transplantation improves motor function and modulates markers of muscle atrophy in diabetic rats
Keywords: Diabetes Mellitus; Neuropatia Diabética.; Disfunção Neuromuscular; Células Tronco Mesenquimais; Atrofia Muscular; CIENCIAS BIOLOGICAS::FISIOLOGIA